Unexpected Functions of NFκB during Germinal Center B-Cell Development: Implications for Lymphomagenesis - Klein, Ulf (Curr Opin Hematol, 2015)
PURPOSE OF THE REVIEW: B-cell tumors originating from the transformation of germinal center (GC) B-cells frequently harbor genetic mutations leading to constitutive activation of the nuclear factor-κB (NF-κB) signaling pathway. This review highlights recent insights into the roles of separate NF-κB transcription factors in GC B-cell development and discusses implications of the results for GC-lymphomagenesis. RECENT FINDINGS: Understanding how aberrant NF-κB-activation promotes tumorigenesis requires the understanding of the role of NF-κB in the tumor-precursor cells. Despite extensive knowledge on NF-κB biology, the function of this complex signaling pathway in the differentiation of GC B-cells is largely unknown. This review will discuss recent findings that revealed distinct roles of separate NF-κB transcription factors during the GC-reaction in the context of GC-lymphomagenesis. Most notably, a single NF-κB subunit, c-REL, was found to be required for the maintenance of the GC-reaction and was associated with the activation of a metabolic program that promotes cell growth. SUMMARY: Identifying the biological roles of the separate NF-κB transcription factor subunits in GC-biology will help to better understand the pathogenic consequences of their constitutive activation in B-cell tumors. This knowledge may be exploited for the development of targeted anti-tumor therapies aimed at inhibiting selectively those components of aberrant NF-κB activity which contribute to pathogenesis.